Gambaran Pengetahuan Sikap dan Tindakan dalam Penggunaan Alat Pelindung Diri pada Cleaning Service di RSUD Prof. Dr. W Z Johannes Kupang - Chornalio Teonly Lulan; Noorce Ch. Berek; Soleman Landi; Andreas Umbu Roga (Yayasan Literasi Sains Indonesia, 2025)
Personal protective equipment is equipment used by workers to protect the body from accidents and diseases resulting from workplace hazards. Data from the Ministry of Manpower, the number of K3 has increased, in 2020 there were 220,740 cases, in 2021 there were 234,370 cases, in 2022 there were 265,334 cases and in 2023 the number of work accident cases was recorded at 370,747 cases. This research aims to determine knowledge, attitudes and actions in the use of protective equipment yourself at the Cleaning Service at RSUD Prof. DR. W. Z. Johannes Kupang. This type of research is descriptive quantitative using a cross sectional method. The research sample was 45 people selected using total sampling technique. Data collection uses questionnaires and interviews. Analysis uses univariate analysis. The results of the study showed that the characteristics of the research respondents included 25 respondents (55.6%) male and 20 female respondents (44.4%), aged 26 – 30 years (33.3%) and 36 – 40 years less (11.1%). %), good education of 44 respondents (97.8%) and less than 1 respondent (2.2%) and good work experience of 16 people (35.6%) and less than 2 people (4.4%). Respondents with good knowledge were 39 respondents (86.7%) and 6 (13.3%) had poor knowledge. Respondents with good attitudes were 32 (71.1%) and 13 (28.9%) had poor attitudes. There were 31 respondents (68.9%) with good actions and 14 respondents (31.1%) with poor actions. It is hoped that hospitals can re-examine the PPE facilities used by the Cleaning Service.